A study on financial cyber-crimes, trends, patterns, and its effects in the economy - Sunny, Abhijith (Addiction & criminology, 2024)
This study focuses on financial cybercrimes, examining their trends, patterns, and impact on the economy. Financial cybercrimes pose significant threats to individuals, businesses, and governments, necessitating a comprehensive understanding of their nature and consequences. By analyzing the evolving tactics and techniques employed by cybercriminals targeting financial systems, institutions, and individuals, policymakers, cybersecurity professionals, and law enforcement agencies can develop effective strategies to prevent and mitigate such attacks. Financial cyber crimes have far-reaching consequences for the economy, resulting in substantial financial losses, decreased trust in online transactions, and disrupted critical infrastructure and services. These impacts extend beyond immediate financial losses, affecting productivity, investment decisions, and consumer confidence. To address the economic impact of financial cybercrimes, stakeholders must prioritize cybersecurity investments, implement robust authentication protocols, and foster cybersecurity awareness. Additionally, comprehensive regulations and international cooperation are necessary to deter cyber criminals and facilitate coordinated responses to cross-border cybercrimes. Through in-depth studies, this research aims to enhance our understanding of financial cybercrimes, identify emerging trends, and develop proactive strategies to mitigate their impact, ultimately safeguarding the economy and building a resilient digital ecosystem.